EFFECT OF PARENTAL EDUCATIONAL STATUS ON LITERACY AND NUMERACY SKILLS OF PRESCHOOL CHILDREN - KONGKONA SONOWAL* (The Journal of Research ANGRAU, 2023)
The study was conducted to understand the effect of parental educational status on the literacy and numeracy skills of their children in their early years. A randomized sample of 300 pre-schoolers from five zones of the Coimbatore district along with their parents’ information accounted for the study conducted in the year 2022. A modified Literacy and Numeracy Assessment Pack was used as a tool for the study. Results revealed that the father’s and mother’s educational status is an influencing factor in preschoolers’ literacy skills (F(4, 2,79)=2.62 p= .035 and F(4, 2,79)=2.67, p= .032, respectively). Whereas, the interaction between the parent’s educational status was also found statistically significant (F(12, 2,79)=2.85,p=.001) in relation to their children’s literacy and numeracy skills. Preschooler’s literacy and numeracy skill influenced by their parent’s educational status and it helps children in their later experiences in shaping children’s brain development.